Nada dan Dakwah: Analisis Diskursus atas Lirik Lagu “Perdamaian” dari Nasida Ria sebagai Komunikasi Dakwah Lewat Musik - Sekar Arum Mandalia; Afif Muhammad; Yeni Huriyani (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, State Islamic University Sunan Kalijaga Yogyakarta, 2022)
Nasida Ria is a qasidah music group from Semarang which was founded in 1975. This group is popular, one of which is through the song titled 'Peace' which was released in 1982. This article attempts to dismantle the link between the lyrics of the song and the global situation that surrounds it. When it emerged in 1982, global conditions were hot due to the cold war and the Iran-Iraq war. While popular again in 2022, 'Peace' is relevant to the conflict between Russia and Ukraine. The lyrics of 'Peace' were analyzed textually, microsociologically, and macrosociologically using a discourse analysis approach from Norman Fairclough. The analysis resulted in the conclusion that from a textual analysis, 'Peace' emphasizes the contradiction aspect in conveying its ideas. In addition, Peace also points to the subject of